The Effect of International Joint Research to the Research Performance: The Case of the Global Research Laboratory and the Basic Research Laboratory Programme. (November 2017) - Kang, Jinwon
Korea has been in a transition from catching-up to post-catching-up period. In this circumstance, the strengthening of basic research is one of the important strategies. This research investigates the main factors influencing research performance through the international joint research (IJR). The literature about determinants of performance of R&D and the effect of IJR to the performance is reviewed. The research performance of IJR will be investigated in comparison with IJR programme and general R&D programme as a result of international and domestic research activities. The comparison about research performance will be performed using independent samples test on the modified impact factor of papers. The main factors influencing the performance are investigated in terms of research budget, capacity, number of researchers and international collaboration on the basis of previous researches. The main finding is that the research capacity is basic requirement to increase the modified impact factor and the main factors influencing research performance through IJR are the network size and the number of contact in this research. Its recommendations, in accordance with this finding, are as follows. The government should support researcher to have more and easier contact with foreign researchers in terms of budget and programme structure and institutional improvement, including evaluation system. The additional budget on the existing programme and easy usage of research budget in the IJR are the good ways to promote the IJR activities through renovation of basic R&D programme structure. The additional credit to the research groups with bigger research networks should be considered in the selection process and ex-post evaluation process. Long-term and sustainable support for the research is the basic requirement to improve the capacity of researchers and obtain better research performance.